2011
DOI: 10.1149/1.3529238
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Solution Synthesis of Crystalline Anatase Nanocolloids for the Fabrication of DSC Photoanodes

Abstract: The production of anatase nanocolloids via a novel aqueous solution synthesis method is described. The process involves forced hydrolysis of 0.2 M TiCl 4 aqueous solution at low temperature ͑80°C͒ leading to fast nucleation of TiO 2 anatase nanoparticles ͑4-5 nm͒. The isolated nanopowders were found to consist predominantly of anatase as the major phase ͑ ϳ 85 wt %͒, possess a very high surface area ͑up to 250-350 m 2 /g͒, and a relatively elevated surface hydroxyl content in comparison with the P25 reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…The 3-5 nm TiO 2 NPs nanoparticles were produced by low temperature (80°C, 30 min) hydrolysis of a 0.125 M TiCl 4 ÁTHF precursor using a method adapted from previous work [30]. To prepare a typical mixed colloid, first an aqueous suspension of P25 (8 wt% in water) was prepared and sonicated for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3-5 nm TiO 2 NPs nanoparticles were produced by low temperature (80°C, 30 min) hydrolysis of a 0.125 M TiCl 4 ÁTHF precursor using a method adapted from previous work [30]. To prepare a typical mixed colloid, first an aqueous suspension of P25 (8 wt% in water) was prepared and sonicated for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The second type of TiO 2 nanoparticles (TiO 2 NPs) consists mostly of anatase nanocrystals (3-5 nm) and a very small fraction of rutile nano-needles [30] (ESI Fig. 1).…”
Section: Oxalate Pre-treatment Of Mixed P25/tio 2 Nps In An Aqueous Mmentioning
confidence: 99%
“…For example, crystallite size and morphology, [9][10][11] crystallinity, 12 phase content, 13 doping, 14,15 and surface groups 16 have been shown to have a significant bearing on the overall efficiency of DSSC devices. Recently, our group reported on aqueous-synthesized anatase nanocolloids 17 possessing very high specific surface area and rich hydroxyl content, properties that were shown to lead via optimized dye (N719) anchoring/coating 18,19 to longer electron lifetime. 16 The films made from this new crop of anatase nanocolloids suffered, however, from small pore size distribution leading to electrolyte diffusion resistance and loss of photocurrent output and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the goals of this paper to report on a new rutile particle variety synthesized via controlled forced hydrolysis 20 that consists of "urchin"-like nanofibrestructured (200-400 nm) particles that proved superior scattering centers in hybrid formulation with our aqueoussynthesized anatase (5-10 nm). 17 Furthermore, we report the optimization of the hybrid paste via the incorporation of P25 nanoparticles that we show via physical and electrochemical characterizations to eliminate losses due to electrolyte diffusion resistance or interfacial charge recombination. Last but not least, it is demonstrated that DSSCs incorporating single-layer screen-printed films of only 5-6 lm in thickness can be built with the novel hybrid paste that compete favorably with double thickness photoanodes based on benchmark commercial paste material.…”
Section: Introductionmentioning
confidence: 99%
“…This is done to reveal the role of surface groups before and after adsorption of two different TiO 2 films; one is a commercial product ("Dyesol") and one made from a hydroxyl-rich anatase variety ("Aqueous") synthesized in our laboratory. 23,24 The influence of these surface binding features on the photovoltaic performance of DSSC devices prepared with the two different TiO 2 electrodes is also discussed on the basis of electrochemical impedance spectroscopic analysis and I-V curve measurements.…”
mentioning
confidence: 99%